Analisis Penetapan Harga Jual Menggunakan Metode Cost Plus Pricing dengan Pendekatan Full Costing - Amelia Putri, Intan; Febri Darmayanti, Elmira; Nusantoro, Jawoto (Expensive: Jurnal Akuntansi dan Keuangan, 2025)
This study aims to determine the pricing method used and to determine the differences in production cost calculations according to Bhista Bakery MSMEs with production cost calculations using the CostPlus Pricing method with a Full Costing Approach. The method used in this study is descriptive with a qualitative approach. Data collection techniques used in this study are observation, interviews, and documentation. Data analysis techniques used include calculating production costs, calculating selling prices, and decision making. The results of this study indicate that there are differences between the calculation of production costs and selling price determination according to Bhista Bakery MSMEs with calculations using the CostPlus Pricing method with a Full Costing approach. In determining the selling price of its products, Bhista Bakery MSMEs lower than using the CostPlus Pricing method with a Full Costing Approach